Family caregivers of children and adolescents with rare diseases: a novel palliative care intervention. Issue Volume 12:Issue e5(2022) (25th July 2019) - Lyon, Maureen E; Thompkins, Jessica D; Fratantoni, Karen; Fraser, Jamie L; Schellinger, Sandra E; Briggs, Linda; Friebert, Sarah; Aoun, Samar; Cheng, Yao Iris; Wang, Jichuan
Abstract : Objective: To develop and pilot test a palliative care intervention for family caregivers of children with rare diseases (FAmily-CEntered pediatric Advance Care Planning-Rare (FACE-Rare)). Methods: FACE-Rare development involved an iterative, family-guided process including review by a Patient and Family Advisory Council, semistructured family interviews and adaptation of two evidence-based person-centred approaches and pilot testing their integration. Eligible families were enrolled in FACE-Rare (the Carer Support Needs Assessment Tool (CSNAT) Approach Paediatric sessions 1 and 2; plus Respecting Choices Next Steps pACP intervention sessions 3 and 4). Satisfaction, quality of communication and caregiver appraisal were assessed. Results: Parents were mean age 40 years, and children 7 years. Children's diseases were rare enough that description would identify patients. All children were technology dependent. Telemedicine, used with four of seven families, was an effective engagement strategy and decreased subject burden. Families found FACE-Rare valuable following a strategy that first elicited palliative care needs and a support plan. Eight families were approached for pilot testing. Of the seven mothers who agreed to participate, six began session 1, and of those, 100% completed: all four FACE-Rare sessions, baseline and 2-week postintervention assessments, and a written pACP which described their preferences for medical decision-making to share with their providers. 100% reported FACE-Rare was helpful. The top three CSNAT concerns were: knowing what to expect in the future, having enough time for yourself and financial issues. Benchmarks were achieved and questionnaires were acceptable to parents and thus feasible to use in a larger trial. Conclusions: FACE-Rare provides an innovative, structured approach for clinicians to deliver person-centred care.